Geriatric depression: prevalence and its associated factors in rural Odisha - Antony, Annu; Parida, Swayam Pragyan; Behera, Priyamadhaba; Padhy, Susanta Kumar (Frontiers in Public Health, 2023)
The population is ageing rapidly and the epidemiological transition has led to an increase in mental disorders in the world. Geriatric depression is masked by multiple comorbidities or natural process of ageing. Our study aims to estimate the prevalence of geriatric depression and assess the factors associated among the elderly with geriatric depression in rural Odisha The study was a multi-stage cross-sectional study conducted in the Tangi block, district Khordha, Odisha, during August 2020-December 2022, among 520 participants selected by probability proportional to size sampling. The eligible 479 elderly were interviewed using A semi-structured interview schedule, Hindi Mental State Examination, Geriatric Depression Scale-15, and Hamilton Depression Rating Scale. The step forward multivariable logistic regression was used to assess the associated factors of depression among elderly persons. Among our participants 44.4%(213) of the elderly were depressed. Substance abuse in family members[AOR:16.7(9.1-30.9)], History of elder abuse[AOR:3.7(2.1-6.7)], Physical dependency [2.2(1.3-3.6)] and Financial Dependency[AOR:2.2(1.3-3.6)] are significant independent risk factors associated with Geriatric depression. Living with children[AOR:0.33(0.18-0.59)] and recreational activity[0.54(0.34-0.85)] are significant protective factors of geriatric depression. Our study found geriatric depression is highly prevalent in rural Odisha. Poor quality of family life and physical and financial dependency was found to be the most significant risk factor for geriatric depression.